2018
DOI: 10.1109/mts.2018.2876213
|View full text |Cite
|
Sign up to set email alerts
|

Activity Trackers for Raising Guide Dogs: Challenges and Opportunities

Abstract: Guide puppy raisers play a crucial role in the process of training assistance dogs supporting mobility of the visually impaired. Recent technological developments bring about a plethora of IT-based solutions, such as canine activity trackers and mobile apps, that could provide novel benefits in supporting the puppy raisers in their important contribution to society. We present an exploratory empirical study of the perceptions and attitudes of puppy raisers and their guide dog center towards such technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Going beyond the interaction perspective, little research has considered the use of commercially available technology for working animals and companion animals to understand the importance of the data such technology capture and process. For instance, by showing differences in volunteer and organizational apprehension to using activity trackers for blind guide dog raising based on a fear of data protection compliance [120], to showing privacy concerns for pet location data is related to the kind of pet and strength of the bond between owner and pet [105], to how technology-supported dog parks could encourage community connections and animal behavioral awareness [52] While the research discussed above indeed investigates the actual technology used on the market, it still lacks critical analysis and evaluation of how such technology is situated in a wider socio-technical context, which is a crucial for engineering an information system [4,10,96,117]. As a result, it is currently difficult to assess how such technology actually informs understanding of animal behavior and in turn steers human action.…”
Section: Background and Motivation-the Need For An Information Systems Perspectivementioning
confidence: 99%
“…Going beyond the interaction perspective, little research has considered the use of commercially available technology for working animals and companion animals to understand the importance of the data such technology capture and process. For instance, by showing differences in volunteer and organizational apprehension to using activity trackers for blind guide dog raising based on a fear of data protection compliance [120], to showing privacy concerns for pet location data is related to the kind of pet and strength of the bond between owner and pet [105], to how technology-supported dog parks could encourage community connections and animal behavioral awareness [52] While the research discussed above indeed investigates the actual technology used on the market, it still lacks critical analysis and evaluation of how such technology is situated in a wider socio-technical context, which is a crucial for engineering an information system [4,10,96,117]. As a result, it is currently difficult to assess how such technology actually informs understanding of animal behavior and in turn steers human action.…”
Section: Background and Motivation-the Need For An Information Systems Perspectivementioning
confidence: 99%
“…Moreover, technical investigations into dataleaks among pet wearables have been reported focusing on Bluetooth Low Energy (BLE) weaknesses, demonstrating the viability of Man-in-the-Middle attacks and data interception [67]. In a study of service dog training, Zamansky and van der Linden [76] found that guide puppy dog raisers were divided on the question of whether dog activity data from such trackers constitutes personal data capable of identifying them (hint: it does), finding an even 3-way split between those who thought it did, those who thought it didn't, and those who had no idea. Perhaps more importantly, the study found that while raisers of puppies were fine with sharing such potentially personal data with the guide center for which they raised these puppies, the management of the center was far less willing to officially use such wearables for the privacy implications they would hold in terms of capturing indirect information of the puppy raisers.…”
Section: Related Work 21 Pet Wearables and Privacy Concernsmentioning
confidence: 99%
“…While such devices can measure activity and sleep patterns, none of them has yet been scientifically validated, and thus are not always appropriate to be used in clinical and scientific settings. Wearables have been investigated in the context of predicting the success of future guide dogs ( [16,13]), impacting the bonding between dog and owner [17,18], and supporting the relationship between guide dog centers and puppy raisers ( [19]). van der Linden et al [20] provide a comprehensive overview of commercially available dog trackers, discussing also their privacy implications.…”
Section: Related Workmentioning
confidence: 99%